Effect of enteric disorders on the growth, age at first calving and first lactation performance and survival of Holstein Friesian heifers - Peddle, Lisa Marie; Margerison, Jean K; Adejoro, Festus (2025)
The UK dairy industry needs to work toward net zero greenhouse gas emissions and elimination of antimicrobial treatment of livestock by 2050. Dairy herd replacements are one of the greatest economic, feed, and carbon footprint (CO2-eq.) costs of milk production, which can be lowered by reducing the age at first calving (AFC), and herd replacement rate (RR) by improving preweaning (PRW) calf health, average daily growth (ADG), feed conversion efficiency (FCE) first lactation milk (FLM) yield and survival. This study aimed to evaluate the incidence and effect of enteric disorders (ED), which required oral rehydration therapy PRW, on the ADG, FCE, AFC, FLM yield, and survival of Holstein Friesian dairy heifers (DH) using 60 DH calves (n-30) that were not treated for ED (NTED) and (n=30) that were treated for ED (TED) PRW. Milk replacer (MR) intake (P=0.030), dry matter intake (P=0.037), ADG (P<0.001), FCE (P=0.047) PRW and weaning weight (WW) (P<0.001), mature weight (MW) (P=0.002) and live weight (LW) (P=0.003) at 12 mo., MW and LW (P=0.002) at first calving, FLM yield (P=0.018), and survival from birth to second lactation (P=0.031) was greater in DH NTED than TED. The AFC (P=0.004), postpartum (pp) interval to first insemination (P=0.007), pp insemination per conception (P=0.066), cost (P=0.004) and CO2-eq./ d calving interval (P=0.049) were lower in DH calves NTED than TED. Calf starter concentrate, chopped cereal straw, and water intake, age at first insemination and conception, body condition score (BCS) at parturition, and pp change in BCS did not differ between DH NTED and TED PRW. In conclusion, the incidence of ED was high, but DH NTED had greater PRW MR, DMI, and ADG, WW. LW and MW at 12 mo. of age, a lower AFC and greater LW and MW first calving, FLM, component yield, and survival rate to second lactation than DH TED PRW.